Cardiac implantable electronic devices replacements in patients followed by remote monitoring during COVID-19 lockdown. Issue 1 (11th January 2021) - Russo, Vincenzo; Rapacciuolo, Antonio; Pafundi, Pia Clara; de Divitiis, Marcello; Volpicelli, Mario; Ruocco, Antonio; Rago, Anna; Uran, Carlo; Nappi, Felice; Attena, Emilio; Chianese, Raffaele; Esposito, Francesca; et al.
Abstract: Aims : Following coronavirus disease (COVID-19) outbreak, the Italian government adopted strict rules of lockdown and social distancing. The aim of our study was to assess the admission rate for cardiac implantable electronic devices (CIEDs) replacement procedures in Campania, the 3rd-most-populous region of Italy, during COVID-19 lockdown. Methods and results : Data were sourced from 16 referral hospitals in Campania from 10 March to 4 May 2020 (lockdown period) and during the same period in 2019. We retrospectively evaluated consecutive patients hospitalized for CIEDs replacement procedures during the two observational periods. The number and type of CIEDs replacement procedures among patients followed by remote monitoring (RM), the admission rate, and the type of hospital admission between the two observational periods were compared. In total, 270 consecutive patients were hospitalized for CIEDs replacement procedures over the two observation periods. Overall CIEDs replacement procedures showed a reduction rate of 41.2% during COVID-19 lockdown. Patients were equally distributed for sex ( P = 0.581 ), and both age [median 76 years (IQR: 68–83) vs. 79 years (IQR: 68–83); P =  0.497]. Cardiac implantable electronic devices replacement procedures in patients followed by RM significantly increased (IR: +211%; P <  0.001), mainly driven by the remarkable increase rate trend of both PM (IR: +475%; P <  0.001) and implantable cardiac defibrillator replacement procedures (IR: +67%, P =  0.01), during COVID-19 lockdown compared with 2019 timeframe. Conclusions : We showed a significant increase trend rate of replacement procedures among CIEDs patients followed by RM, suggesting the hypothesis of its increased use to closely monitoring and to optimize the hospital admission time during COVID-19 lockdown.